COMMON SYNDROMES ASSOCIATED WITH AUTISM IN YOUNG CHILDREN - Koukoutsi, Ariadne; Tsala, Danae; Tsipi, Alexia (Open Schools Journal for Open Science, 2025)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition that affects social interaction, communication, and behavior. In many cases, ASD coexists with other syndromes that contribute to the diversity of symptoms observed in young children. This presentation explores common syndromes associated with ASD—such as Fragile X Syndrome and Down Syndrome—and highlights the importance of early identification, understanding of behavioral and social challenges, and the need for targeted interventions. The aim is to enhance awareness and support more effective, individualized care.